To what extent the presence of real‐strength tropical cyclones influences the estimation of atmospheric intraseasonal oscillation intensity?. (14th April 2015) - Bi, Mingyu; Li, Tim; Shen, Xinyong; Peng, Melinda
Abstract An idealized dataset that contains a background seasonal mean state, a reference intraseasonal oscillation (ISO) state and real‐strength tropical cyclones (TCs) was constructed, in order to examine to what extent the presence of the real‐strength TCs may impact the overall ISO strength over the western North Pacific. The averaged ISO strength (measured by combined 850‐hPa zonal and meridional wind fields) increases by 9% when the realistic TCs are included. The percentage increase of the overall ISO strength depends on the variable used. It is doubled (reduced to 3%) when the vorticity (stream function) is used as the estimated variable.